Intracellular Electrochemical Nanomeasurements Reveal that Exocytosis of Molecules at Living Neurons is Subquantal and Complex. (3rd March 2020) - Larsson, Anna; Majdi, Soodabeh; Oleinick, Alexander; Svir, Irina; Dunevall, Johan; Amatore, Christian; Ewing, Andrew G.
Abstract: Since the early work of Bernard Katz, the process of cellular chemical communication through exocytosis, quantal release, has been considered to be all or none. Recent evidence has shown exocytosis to be partial or "subquantal" at single‐cell model systems, but there is a need to understand this at communicating nerve cells. Partial release allows nerve cells to control the signal at the site of release during individual events, for which the smaller the fraction released, the greater the range of regulation. Herein, we show that the fraction of the vesicular octopamine content released from a living Drosophila larval neuromuscular neuron is very small. The percentage of released molecules was found to be only 4.5 % for simple events and 10.7 % for complex (i.e., oscillating or flickering) events. This large content, combined with partial release controlled by fluctuations of the fusion pore, offers presynaptic plasticity that can be widely regulated. Abstract : Partielle chemische Freisetzung ermöglicht es Nervenzellen, das Signal am Ort der Freisetzung während einzelner Ereignisse zu steuern. Der Regulierungsbereich ist umso größer, je kleiner die freigesetzte Fraktion ist. Intrazelluläre Elektrochemie in Kombination mit theoretischer Modellierung zeigt, dass der Gehalt an vesikulärem Oktopamin sehr groß und die exozytotische Fraktion, die aus einem lebenden neuro‐muskulären Neuron einer Drosophila ‐Larve freigesetzt wird, sehr klein ist.